Identification of the features of structural-phase transformations in the processing of waste from the production of high-alloy steels - Borysov, V.; Solomko, T.; Yamshinskij, M.; Lukianenko, I.; Tsymbal, B. M.; Andreev, A.; Bratishko, V.; Bilko, T.; Rebenko, V.; Chorna, T.; Цимбал, Б. М. (ПП «ТЕХНОЛОГІЧНИЙ ЦЕНТР», 2021)
This paper reports a study into the peculiarities of the structural-phase composition of the alloy obtained by using anthropogenic waste from the production of high-alloy steels involving reduction melting. That is necessary for determining the technological parameters that could help decrease the loss of alloying elements in the process of obtaining and using a doped alloy. This study has shown that at an O:C ratio in the charge of 1.84, the alloy consisted mainly of the solid solution of carbon and alloying elements in α-Fe. The manifestation of Fe3C carbide with alloying elements as substitution atoms was of relatively weak intensity. At the O:C ratios in the charge of 1.42 and 1.17, there was an increase in the intensity of the Fe3C carbide manifestation. At the same time, the emergence of the carbide compounds W2C·Mo2C and WC was identified. Several phases with different content of alloying elements were present in the microstructure images. Cr content in the examined areas changed in the range of 0.64–33.86 % by weight; W content reached 41.58 % by weight; Mo –19.53 % by weight; V – 18.55 % by weight; Co – 3.95 % by weight. The carbon content was in the range of 0.28–2.43 % by weight. Analysis of the study results reveals that the most favorable ratio of O:C in the charge was 1.42. At the same time, the phase composition was dominated by a solid solution of the alloying elements and carbon in α-Fe. The share of the residual carbon concentrated in the carbide component was in the range of 0.52–2.11 % by weight, thereby ensuring the required reduction capability of the alloy when used. The study reported here has made it possible to identify new technological aspects of obtaining an alloy by utilizing anthropogenic waste, and whose indicators provide for the possibility of replacing part of standard ferroalloys when smelting steels without strict restrictions on carbon content.
Keywords: oxide anthropogenic waste; alloy steel scale; reduction melting; X-ray phase studies